GLIMR: A GIS-BASED METHOD FOR THE GEOMETRIC MORPHOMETRIC ANALYSIS OF ARTIFACTS. (August 2015) - Davis, Loren G.; Bean, Daniel W.; Nyers, Alex J.; Brauner, David R.
Abstract : Archaeology's participation in the digital renaissance of the twenty-first century requires adequate operationalization of technological methods, such as three-dimensional scanning. Here, we describe and demonstrate a geographic information systems-based lithic morphometric research (GLiMR) software approach. GLiMR accurately and rapidly handles a sequence of ArcGIS procedures to extract geometric morphometric data from 2D and 3D scan files that are impractical to record by hand, opening new doors to the analysis of lithic artifacts. GLiMR generates three main types of geometric properties: shape data, topographic data, and domain aggregate data. These data can be extracted in ways that support other analyses of artifact form, including generalized Procrustes analysis, principal components analysis, and cluster analyses. We illustrate the use of GLiMR by presenting a basic case study that compares the geometric morphometry of Western Stemmed Tradition projectile points found in two cache features at Idaho's Cooper's Ferry site and from other sites in the Columbia River Plateau region of the Pacific Northwest. Cluster analyses of the generalized Procrustes analysis of 3D landmarks from Cooper's Ferry cache points fail to separate the two caches from one another on the basis of their geometric morphometric attributes. We interpret these results to suggest that these stemmed projectile points were probably created by persons who shared a specific set of technological production guidelines for the manufacture of Western Stemmed Tradition projectile points. Cluster analyses indicate that Cooper's Ferry Western Stemmed Tradition projectile points can be morphometrically separated from stemmed points found at other regional sites; however, significant overlaps were seen among stemmed projectile points from the Pilcher Creek site, which may suggest the existence of contemporaneous information sharing networks or macroband territorial movements.